Phosphoglycerol-type wall- and lipoteichoic acids are enantiomeric polymers differentially cleaved by the stereospecific glycerophosphodiesterase GlpQ - Walter,A; Unsleber,S; Rismondo,J; Jorge,AM; Peschel,A; Gründling,A; Mayer,C (2020)
ABSTRACT The cell envelope of Gram-positive bacteria generally comprises two types of polyanionic polymers, either linked to peptidoglycan, wall teichoic acids (WTA), or to membrane glycolipids, lipoteichoic acids (LTA). In some bacteria, including Bacillus subtilis strain 168, WTA and LTA both are glycerolphosphate polymers, yet are synthesized by different pathways and have distinct, although not entirely understood morphogenetic functions during cell elongation and division. We show here that the exo-lytic sn -glycerol-3-phosphodiesterase GlpQ can discriminate between B. subtilis WTA and LTA polymers. GlpQ completely degrades WTA, lacking modifications at the glycerol residues, by sequentially removing glycerolphosphates from the free end of the polymer up to the peptidoglycan linker. In contrast, GlpQ is unable to cleave unmodified LTA. LTA can only be hydrolyzed by GlpQ when the polymer is partially pre-cleaved, thereby allowing GlpQ to get access to the end of the polymer that is usually protected by a connection to the lipid anchor. This indicates that WTA and LTA are enantiomeric polymers: WTA is made of sn -glycerol-3-phosphate and LTA is made of sn -glycerol-1-phosphate. Differences in stereochemistry between WTA and LTA were assumed based on differences in biosynthesis precursors and chemical degradation products, but so far had not been demonstrated directly by differential, enantioselective cleavage of isolated polymers. The discriminative stereochemistry impacts the dissimilar physiological and immunogenic prope